ECONOMIC ANALYSIS OF MINIMUM STRUCTURE PLATFORM USE FOR OIL FIELD DEVELOPMENT - RIZKI BALYA (Nim: 250 03 060); Pembimbing : Dr.Ir. Reini D. Wirahadikusumah, M.
Deline of Indonesian oil production causes government has to find new ways to raise oil production. One of the ways that can be performed is by developing oil fields with reservoirs containing insignificant amount of oil in offshore area that were undeveloped for economic reason. The development is performed using minimum structure platform replacing conventional platform to reduce initial investment. Even though the utilization of this platform has benefit by reducing initial investment, but the limitation in number of wells that can be installed causes this platform only effective if it is used at oil fields with certain oil production rate and reserve. This analysis is intended to determine in what conditions this platform can be used optimally. The analysis was performed by computing net present value and internal rate of return for fields with various production rates and reserves based on oil field development model using minimum structure platform. Cash flow was determined by identifying cost and income components which occur during the life cycle of an oil field. The value of cost and income components is obtained by performing estimation to the model performed at preliminary level. Result of analysis shows that in condition crude oil price is higher than US$ 50 per barrel, oil field development using minimum structure platform is economically visible for oil fields with production rate over 1500 bopd and reserve above 2,0 MMSTB.